NURSING PROFESSIONALS AND PSYCHIATRIC ADMISSION IN GENERAL HOSPITAL: PERCEPTIONS AND PROFESSIONAL TRAINING - Marciana Fernandes Moll; Lucas Duarte Silva; Felipe Henrique de Lima Magalhães; Carla Aparecida Arena Ventura (Universidade Federal do Paraná, 2017)
Qualitative study aimed to investigate how the nursing staff perceives psychiatric care beds in a general hospital and assess whether they are capable toassist people with mental disorders. Data was collected from May to July 2016, in a general hospital in the state of Minas Gerais and 31 nurses participated in the study. Semi-structured interviews were used to collect information, and the data obtained was subsequently submitted to content and thematic analysis. It was found that the participants felt uncomfortable withpsychiatric beds in the general hospital, which may be related to their lack of skills to provide care for people with mental disorders. Therefore, it is necessary to develop educational planning, especially for nursing technicians, in order to make them able to assist these patients.